Technology Platforms in Europe: an empirical investigation - Lisa De Propris; Carlo Corradini (WWWforEurope, 2013)
In the last decades, innovation activity has been defined by an increasing complexity and a faster pace of the underlying technological change. Accordingly, several studies have shown that competitive systems of innovation benefit from being able to build upon a wide but integrated spectrum of technological capabilities characterised by a sustained dynamism in the level of inter-sectoral technology flows. In this context, technological platforms – defined as knowledge and scientific launching pads that spin out of key enabling technologies - may create the opportunity for technological externalities to take place across a set of related sectors through a swarm of increasingly applied and incremental innovations. In this report, we look at the presence and determinants of these technological platforms across EU Countries and explore the mechanisms through which these influence inter sectoral technology spillovers, thus fostering technological shifts and technological synthesis within the broader economy. Using data on patents and patent citations obtained from the PATSTAT-CRIOS database, covering all patent applications made to the European Patent Office (EPO), we try to model the systemic nature of technology platforms. In particular, our aim is to provide empirical evidence that the presence of key enabling technologies at the base of the platform may lead to a more sustained interaction across second tier innovations characterised by a “distant” knowledge base. Then, we endeavour to investigate the relationship that may take place between this process and the role played by the national dimension.
Keywords: O3; O31; O32; O33; O38; 330; Clusters; ecological innovation; industrial innovation; innovation; innovation policy; new technologies; patents; socio-ecological transition; sustainable growth